Potencial evocado miogênico vestibular em mulheres com migrânea vestibular - Morganti, Ligia Oliveira Gonçalves [UNIFESP] (2016)
Introduction: Vestibular Migraine (MV) is considered the main cause of recurrent spontaneous vertigo. Among the tests of vestibular function evaluation, the vestibular evoked myogenic potential (VEMP) is a relatively new and easy method with recognized clinical practice utility. Objective: To describe the results of cervical and ocular VEMP in women with MV and compare with the responses obtained in normal individuals. Methods: cross-sectional study with women with MV according to Barany Society / International Headache Society 2012-2013 criteria and controls. The tests were performed using tone burst stimulus, with 500 Hz and 1000 Hz, in addition to clicks, used only for cervical VEMP. Results were compared between the two groups and the stimulus type/frequency. Results: The median age of patients was 38 years. The average of onset time of headache was 22.1 years and dizzines 10.32 years. cVEMP: the study group had largest interamplitudes compared to individuals from control group. The asymmetry index was greater in the patient group just for click stimulus. Within each group, the latencies and interamplitudes were larger for tone burst stimulus of 500 Hz, followed by 1000 Hz and click. There was no difference in the asymmetry index, for each different stimulus, in both group. oVEMP: There was no difference between the groups, the values of latencies, interamplitudes and asymmetry indices. Within each group, the latencies and interamplitudes were larger for 500Hz tone burst stimulus. Conclusions: female patients with MV out of disease crisis period, tend to have higher response amplitudes on cVEMP and greater asymmetry index in the cVEMP with Click stimulus when compared to controls. The TB stimulus in frequency of 500 Hz displays response wityh largest interamplitudes and latencies, followed by 1,000 Hz and click in both controls and individuals with MV. There is no difference, in both groups, between the different stimuli, for the asymmetry index values